The effectiveness of antimicrobial photodynamic therapy for treating peri-implant diseases in people with type 2 diabetes mellitus: a systematic review and meta-analysis - Zhen-Fang Ni; Ping Zhang; Yan-Fei Zhang (Photodiagnosis and Photodynamic Therapy)
Objective: This systematic review and meta-analysis rigorously assesses the efficacy of antimicrobial photodynamic therapy (aPDT) on peri‑implant diseases in patients with type 2 diabetes mellitus(T2DM). Methods: Five databases were systematically searched from inception to December 2024. Primary outcomes included probing depth (PD), bleeding on probing (BOP), marginal bone level (MBL), and plaque scores; secondary outcomes were interleukin‑6 (IL‑6) and tumor necrosis factor‑α (TNF‑α). Prediabetic individuals were excluded because peri-implant diseases mechanisms differ substantially from those in T2DM. Results: Five trials (98–235 participants per outcome) were included. In short‑term (≤3 months), aPDT yielded significant reductions in PD (SMD –0.41, –0.73 to –0.09; I²=0 %), BOP (−0.81, −1.51 to −0.12; I²=76 %), and plaque scores (–0.51, –0.80 to –0.22; I²=0 %), with no significant change in MBL (–0.25, –0.62 to 0.12; I²=35 %). In short‑term, IL‑6 decreased (–0.33, –0.62 to –0.04; I²=0 %), whereas TNF‑α did not (–0.17, –0.50 to 0.17; I²=0 %). In medium‑term (3–12 months), benefits persisted for PD (–1.90, –3.50 to –0.30; I²=94 %), BOP (−1.11, −1.90 to −0.32; I²=81 %), MBL (–0.72, –1.01 to –0.44; I²=0 %), and plaque scores (–0.54, –0.96 to –0.12; I²=28 %). In medium‑term, IL‑6 (–0.30, –0.64 to 0.04; I²=0 %) and TNF‑α (–0.20, –0.62 to 0.22; I²=0 %) remained reduced but with no statistically significant differences. Conclusion: APDT confers significant short‑ and medium‑term improvements in peri‑implant clinical and inflammatory outcomes among T2DM. However, the results should be interpreted with caution due to limitations in the number of included trials and length of follow-up.